Cytokine profile of patient’s sera of Leptospirosis to OMP of Leptospira interrogans serovar tarassovi - Latha, MM Prem; Kaur, IR; Avasthi, R; Dey, AB; Chaudhry, R (Asian Journal of Medical Sciences, 2015)
Aims and Objectives: In the past decade, Leptospirosis has emerged as a globally important emerging infectious disease. Leptospires have several chemical components such as Lipoproteins, glycolipoproteins which are toxic and participate in the pathogenesis of the disease. This study was focused to find out the immune response of outer membrane proteins (OMPs) of Leptospira interrogans serovar tarassovi by estimating the cytokine profile and antibody levels from cases of Leptospirosis. Materials and Methods: A total of 120 blood samples were collected from patients (90 male/30 female) presenting with acute febrile illness and fulfilling the criteria of clinical diagnosis of Leptospirosis. All the 120 samples & 40 healthy controls were subjected to ELISA (IgM serion), MAT and Leptospira interrogans serovar tarassovi IgM ELISA and also to detect TNF? and IL-6 levels using (BD Opt EIA Human IL-6 & TNF? ELISA kits). Results: Sera which were found to be reactive in L. interrogans serovar tarassovi OMP IgM ELISA had significant levels of TNF? and IL-6 and antibody titres in ELISA and MAT. Conclusions: Patients from Group I had significant levels of TNF? in the serum i.e., p = 0.02 which indicates the pro-inflammatory Th1 response as TNF? are macrophage derived cytokine mediators. The IL-6 level of Group I, II, III were significantly higher than the Group IV (p = 0.02) suggesting that Th2 anti-inflammatory response seen in majority of these cases which has a protective role in leptospirosis. Asian Journal of Medical Sciences Vol.7(1) 2015 93-95